What lies beneath peer acceptance in adolescence? Exploring the role of Nucleus Accumbens responsivity to self-serving and vicarious rewards. (November 2018) - Meuwese, Rosa; Braams, Barbara R.; Güroğlu, Berna
Highlights: Higher sensitivity for self-serving rewards is related to lower peer acceptance. Peer acceptance is not related to Nucleus Accumbens activity during vicarious wins. Findings highlight the importance of neural reward-processing in peer relationships. Abstract: Peer relationships play an important role in adolescent social development. Adolescence is also a sensitive period for reward-related processing where Nucleus Accumbens (NAcc) shows peak levels of activity. To investigate the role of reward-related neural processes in peer relationships, we scanned 31 adolescents (16 boys, 15 girls) from 12 to 17 years old and had their classmates rate their likability and dislikability. Using these ratings, we calculated levels of peer acceptance (i.e., likability minus dislikability scores). Participants played a social gambling paradigm in the scanner where we examined NAcc responses to winning for self and winning for best friends. We showed that acceptance by peers was related negatively to activation patterns in the NAcc when winning money for self. Peer acceptance was not related to NAcc activity during vicarious reward processing where participants won money for their best friend. These results point in the direction of an underlying neural mechanism indicating that peer interactions of well-liked adolescents are characterized by a lower focus on benefits for self.